Nutrition Education Effect in Increasing Knowledge and Ability to Interpret Nutrition Facts in Adolescents - Meylinda, Jovita Octa; Arinda, Ditia Fitri; Yuliana, Indah; Sari, Desri Maulina (International Journal of Integrated Health Sciences, 2024)
Objective: To evaluate the effectiveness of nutrition education on the understanding and proficiency in interpreting nutrition labels among adolescents aged 16-18 years..Methods: This quantitative study adopted quasi-experimental and control group designs with a pre-test and post-test approach. The sample size included 60 participants, divided into 2 equal groups, receiving education through lecture method and leaflets, respectively. The intertervention was conducted one day in group 1 and group 2, respectively. Sample selection was conducted using a simple random sampling method. Data were collected through a knowledge questionnaire and details on reading ability were obtained using an interpreting ability checklist through pre-tests and post-tests conducted at the same day. The retrieved data were analyzed using the Wilcoxon Signed Rank Test and the Mann-Whitney U Test (α=0.05).Results: Nutrition education is shown to enhance the understanding (p-value=0,026) and proficiency of students in interpreting nutrition facts (p-value=0,064).Conclusion: Nutrition education had a positive impact on the understanding and skill of adolescents in reading nutrition facts. Thus, developing educational materials that can be readily applied in daily life will help consumers in making more nutritionally informed choices when selecting packaged foods.